Resting State EEG Related to Mathematical Improvement After Spatial Training in Children - Zhang, Da-Wei; Zaphf, Anna; Klingberg, Torkel (Frontiers in Human Neuroscience, 2021)
Spatial cognitive abilities, including mental rotation (MR) and visuo-spatial working memory (vsWM) are correlated with mathematical performance, and several studies have shown that training of these abilities can enhance mathematical performance. Here we investigated the behavioral and neural correlates of MR and vsWM training combined with number line (NL) training. Fifty-seven children, aged 6-7, performed 25 days of NL training combined with either vsWM or MR and participated in an EEG-session in school to measure resting state activity and steady-state visual evoked potentials during a vsWM task before and after training. Fifty children, aged 6-7, received usual teaching and acted as a control group. Compared to the control group, both training groups improved on a combined measure of mathematics. Cognitive improvement was specific to the training. Significant pre-post changes in resting state EEG (rs-EEG), common to both training groups, were found for power as well as for connectivity, with no significant differences in rs-EEG -changes between the vsWM and MR groups. Two of the common rs-EEG changes were correlated with mathematical improvement: (1) an increase in connectivity between the central frontal lobe and the right parietal lobe in frequencies ranging from 16 to 25 Hz, and (2) an increase in connectivity between the left frontal lobe and the right parietal lobe ranging from 23 to 25 Hz. These results indicate that changes in fronto-parietal connectivity are related to an increase in mathematical performance, which thus might be a useful measure in further investigations of mathematical interventions in children.